Pengetahuan Pedagogi Isi Kandungan Guru Sains Sekolah Rendah dalam Mengajarkan Pemikiran Sains Keusahawanan: Satu Kajian Kes (Sains Humanika, 2013)
This qualitative study aims to determine the science teachers’ pedagogical content knowledge (PCK) and its components applied by them in the teaching of entrepreneurial science thinking (EST) by using the EST module. The teaching of entrepreneurial science thinking is an effort to cultivate students’ thinking to apply their scientific knowledge in everyday situation in a creative and inovatif way, including with the orientation of entrepreneurship thinking. Two science teachers, who have educational background and experience in using the EST module to teach science in primary schools, are involved in this study. The qualitative data was analysed by using the six phases of Shulman‘s pedagogical reasoning model (understanding, transformation, instruction, assessment, reflection, and new understanding) in each thinking step in the EST module (observe, new ideas, innovation, creativity, and society). It was found that the PCK component which is always referred to by both teachers is knowledge of students, while the knowledge component of PCK which is seldom applied by the science teachers is knowledge of the contexts. Meanwhile, pedagogical knowledge and content knowledge are applied to all steps of the EST module, but not referred to in all the pedagogical phases of Shulman’s reasoning model. The findings of this study indicate that knowledge of the students is the most important component of teaching EST in primary schools. This study also supports the previous research stated that to enhance creativity and innovation among students, teachers must have knowledge about their students.
Keywords: Pedagogical Content Knowledge (PCK); Entrepreneurial Science Thinking (EST); Shulman‘s pedagogical